PENGARUH STATUS GIZI TERHADAP KUALITAS HIDUP ORANG DENGAN HIV/AIDS (ODHA) YANG MENERIMA TERAPI ARV - Rizka Gia Novita (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2022)
Background: Quality of life in people living with HIV/AIDS (PLWHA) is an important component of evaluating treatment. In other hand, nutritional status plays an important part in disease progression, which eventually affects the quality of life. Therefore, the correlation between nutritional status and quality of life must be further studied. Objective: to study the correlation between nutritional status and quality of life of PLWHA receiving ART Methods: cross-sectional analytical research using Body Mass Index (BMI) and WHOQOL-HIV BREF Questionnaire to evaluate the quality of life of PLWHA. Bivariate and multivariate analysis were done using chi-square and logistic regression, respectively. Results: The results showed that there was no relationship between nutritional status and quality of life. This study found a relationship between age, stigma, and depression with quality of life in people living with HIV who received ARVs. Conclusion: The integration of psychologists in the treatment of HIV/AIDS is also recommended considering that depression plays a role in the quality of life of PLWHA. Education to the community to reduce stigma should also be carried out. Keywords: Nutritional status, Quality of Life, People Living With HIV/AIDS, Antiretroviral Therapy